1997
DOI: 10.1046/j.1365-2958.1997.4051770.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the repressor (BlaI) of β‐lactamase synthesis in Staphylococcus aureus

Abstract: SummaryPurified BlaI, the putative repressor of the ␤-lactamase operon in Staphylococcus aureus, binds specifically to two regions of dyad symmetry (operators) located in the blaZ-blaR1 intergenic region. BlaI binds with similar affinity to the two regions and to the related sequence upstream of the mec gene found in methicillin-resistant strains of S. aureus, providing physical evidence for the cross-talk previously observed between these systems. A change from a lysine in the N-terminus of BlaI to an alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 28 publications
(31 reference statements)
6
103
0
Order By: Relevance
“…This event triggers the activation of the putative cytoplasmic metalloprotease motif of BlaR1 by self-proteolysis (8,12). In S. aureus, the ␤-lactamase induction correlates with BlaI proteolysis between residues Asn 101 and Phe 102 , and it is postulated that the activated form of BlaR1 proteolyses BlaI (12)(13)(14)(15). The blaR2 gene could be involved in this process or in the activation of BlaR1, but our recent studies in a recombinant Bacillus subtilis harboring a plasmid carrying the bla divergeon show contrasting results with those in S. aureus and suggest that the inactivation of BlaI in Bacillus is mediated by the binding of a coactivator (16).…”
mentioning
confidence: 99%
“…This event triggers the activation of the putative cytoplasmic metalloprotease motif of BlaR1 by self-proteolysis (8,12). In S. aureus, the ␤-lactamase induction correlates with BlaI proteolysis between residues Asn 101 and Phe 102 , and it is postulated that the activated form of BlaR1 proteolyses BlaI (12)(13)(14)(15). The blaR2 gene could be involved in this process or in the activation of BlaR1, but our recent studies in a recombinant Bacillus subtilis harboring a plasmid carrying the bla divergeon show contrasting results with those in S. aureus and suggest that the inactivation of BlaI in Bacillus is mediated by the binding of a coactivator (16).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that the signaling pathway responsible for β-lactamase synthesis requires sequential cleavage of the regulatory proteins BlaR1 and BlaI. Following exposure to β-lactams, BlaR1, a transmembrane sensor-transducer, cleaves itself (17,18). Zhang et al (18) hypothesize that the cleaved protein functions as a protease that cleaves the repressor BlaI, directly or indirectly (an additional protein, BlaR2, may be involved in this pathway) and allows blaZ to synthesize enzyme.…”
mentioning
confidence: 99%
“…CopY, a member of the Bla/ Mec repressor family, is the archetypical prokaryotic copper regulated repressor [20]. In the DNA binding state, CopY binds one Zn(II) ion in a -CxCxxxxCxC-motif.…”
Section: Regulation Of the Cop Operon And Copymentioning
confidence: 99%
“…To maintain DNA binding activity Zn(II) must be bound to the protein [21]. Within the Bla/Mec family of repressors the affinity for DNA is strongly linked to the formation of dimers [20]. Cu(I) ions displace the Zn(II) in the CopY metal binding site, prompting the protein to lose affinity for DNA [16].…”
Section: The Structure Of Copymentioning
confidence: 99%